Metode Pengasuhan dalam Pembentukan Karakter Religius di Panti asuhan Yatim Putra Islam Yogyakarta - Mgr Sinomba Rambe; Wantini Wantini; Ahmad Muhammad Diponegoro (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2023)
Abstract The character of a child is closely related to the upbringing he receives from his caregiver; in other words, good parenting will also have a positive impact on the child, and the character possessed by a child is a reflection of the parenting style provided by the caregiver. In order to avoid deviations in the child's character, several good parenting methods are needed in the formation of the child's religious character. This study aims to analyze the parenting style applied by the Yogyakarta Islamic Boys' Orphanage in shaping the religious character of the orphanage's children. This study uses descriptive qualitative research, which provides an overview or description of empirical facts from observations and interviews and is supported by documentation about the methods used by the Yogyakarta Boys' Orphanage in shaping the religious character of children in orphanages. The results of this study indicate that Islamic orphanages use a variety of parenting methods, such as the da'wah method of instilling knowledge, the compassion method, the exemplary method, the advice method, the habituation method, and other methods in the form of worship, education, social interaction, and muamalah. Of course, when using this method, one must always adhere to Islamic parenting principles, such as